Neuropharmacological and Antidiarrheal Potentials of Duabanga grandiflora (DC.) Walp. Stem Bark and Prospective Ligand–Receptor Interactions of Its Bioactive Lead Molecules - Israt Jahan; Mohammad Forhad Khan; Mohammed Abu Sayeed; Laiba Arshad; Md. Amjad Hossen; Md. Jakaria; Duygu Ağagündüz; Md. Areeful Haque; Raffaele Capasso (Current Issues in Molecular Biology, 2022)
Duabanga grandiflora (DC.) Walp. is an ethnomedicinally significant plant used to treat various illnesses, but there is little scientific evidence to support its use. This study explored the pharmacological activities of methanol extract of D. grandiflora stem barks (MEDG) through in vivo approaches in Swiss albino mice and a computer-aided molecular approach. The forced swimming test (FST), tail suspension test (TST), elevated plus maze (EPM), and hole board test (HBT) were used to determine anti-depressant and anxiolytic activity in experimental mice. In addition, anti-diarrheal studies were performed using castor oil-induced diarrhea, castor oil-induced enter pooling, and the charcoal-induced gastrointestinal motility test. MEDG showed substantial depletions in the immobility times in both FST and TST after treatment with the MEDG extract, whereas moderate anxiolytic activity was manifested at a higher dose (400 mg/kg) compared with the control. Correspondingly, MEDG extract revealed a significant reduction in wet feces and decreased the small intestinal transit of charcoal meal in castor oil-induced diarrhea and charcoal-induced gastrointestinal motility test. In the computer-aided molecular approaches, vanillin displayed a promising binding score for both anxiolytic and anti-diarrheal activities, while duabanganal C showed a promising score for the anti-depressant activity. The present experimental findings along with a computer-aided model conclude that MEDG could be a possible Phyto therapeutic agent with potential anti-depressant, anxiolytic and anti-diarrheal activity.